Pattern and process in the largest primeval beech forest of Europe (Ukrainian Carpathians). (3rd October 2014) - Hobi, Martina L.; Commarmot, Brigitte; Bugmann, Harald; Woods, Kerry
Abstract Questions Are the structural characteristics of natural beech forests predominant on small monitoring plots representative of the large‐scale features of these forests? Do the findings of our large‐scale investigation support the hypothesis that this primeval beech forest is shaped by fine‐scale processes, or is there evidence that high‐severity disturbance events have affected its structure? Location Ukrainian Carpathians, Uholka‐Shyrokyi Luh, the largest primeval beech forest in Europe, covering 102.8 km2. Methods On 314 (500 m2) circular plots, systematically distributed across the forest, all living and dead trees with a DBH ≥6 cm were assessed. Lying deadwood, tree regeneration, the size of canopy gaps and the number of canopy layers were recorded. Spatial analyses were conducted using Moran's I. Dendrochronological analysis was used to reconstruct tree ages and growth patterns. Results The forest is characterized overall by a density of 435.0 ± 12.2 ha−1 (mean ± SE) living trees, a basal area of 36.6 ± 0.8 m2·ha−1, a volume of living trees of 582.1 ± 13.5 m3·ha−1 and a total deadwood volume of 162.5 ± 8.4 m3·ha−1. Beech is the dominant species (97.3 ± 0.7%, by basal area), interspersed with mostly deciduous species with moderate shade tolerance. The forest canopy is multi‐layered, with a high abundance of old trees, and with canopy gaps rarely larger than the crown projection area of a few trees. Conclusions The results lend support to findings from small monitoring plots, but our landscape approach allows a reliable estimation of key forest characteristics such as basal area and standing volume, which tend to be overestimated in studies on subjectively placed small monitoring plots. We conclude that disturbance events of moderate or higher severity have left only few discernible traces in forest structure or species composition. All findings suggest that this forest is characterized by a mainly small‐scale disturbance regime, leading to a homogeneity of forest characteristics of the living stand at larger spatial scales and causing only minor fluctuations around the average values of forest parameters observed.